DEVELOPMENT OF THE PHARMACEUTIC CRYSTALLIZATION PROCESS USING PLASMODIUM FALCIPARUM, A DERIVATIVE OF THIOSEMICARBAZONE - A, GEETHA; C, JEEVARATHINAM; GV, PANDIAN (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The current study was designed with the goal of analyzing novel derivatives of organic and semi-organic NLO molecules that are just entering this field as the foundation for future therapeutic development. Methods: Thiosemicarbazones (TSC) are semicarbazide analogs that have sulfur atoms in place of oxygen atoms. The greatest number of therapeutic treatments for various disorders are also being used carbonyl compounds. These two types of organic compounds were combined, and their replacement with crystal growth procedures using solution growth was tested as an antibiotic for a few fastidious and nonfastidious species. The preparation of meta-substituted benzaldehydes using TSC. Tests were conducted with this single component. The following experimental technique was used to determine the antibacterial activity of Plasmodium falciparum. Half-inhibitory maximum (IC50) by calculation technique, cell viability % calculation method, and MTT assay by colorimetric method. Results: Method using agar discs. Using the agar disc diffusion method to measure the inhibition zone width and comparing the minimal inhibitory concentration (MIC) and inhibition zone width of available antibiotics against the aforementioned organism using data from the EUCAST and NCCLS databases, The absolute, relative, and mound slope values of an antibiotic that is currently on the market may be determined using the GraphPad Prism software; the epidemiological cutoff value can be determined using the ECOF Finder software; and the nature of the antibiotic can be determined using the WHONET 5.6 software. The newly developed antibiotics’ size and structure are contrasted with the structures of commercially available antibiotics and living organisms. Conclusion: The design of new drugs using novel derivatives of organic and semiorganic NLO molecules is based on the in vitro method of analysis, which has recently been introduced to this field. P. falciparum has an extremely low MIC value (0.625 μg/mL) against TSCMNB. The MIC break points are always larger than, not equal to, the MIC values and fall within the range of 110 μg/mL–130 μg/mL. We concluded that all of the novel compounds exhibit a susceptible form of inhibition.